DELIR DAN SEKSUALITAS INFANTIL DALAM “AL-FIRÂSH AL-SHAGHÎR” KARYA YEHIA HAKKI - As. Rakhmad Idris (Kelasa, 2017)
AbstractLiterary works are born from the social womb of society. Authors are just painters of everydayphenomena and human behaviors. The story of Yehia Hakki's "Al-Firâsh Al-Shaghîr" (FS) is one ofthe most interesting fictional stories of the Middle East to be studied. The main character in the FSshort story has a different mental predisposition from ordinary people. He is suspected of having adelirious and infantile desire controlled by his dreams to prove the psychological phenomenon, thewriter conducts a study using Freud's psychological approach. In his theory, Freud describes theconcept of id, ego, and superego, oedipus complex, and self-defence This study finds thepsychological phenomenon of the "young man" who "loves "his mother thus he considers thefather as a rival, and also has a pent-up desire to a black woman who is cold like a wax statue. Thedesires and pent-up desires of the main character in the FS show the delirious phenomenon ofinfantile delirium and passion in the young man. AbstrakKarya sastra lahir dari rahim sosial masyarakat. Pengarang hanyalah pelukis fenomena kesehariandan tingkah laku manusia. Cerpen “Al-Firâsh Al-Shaghîr" (FS) karya Yehia Hakki merupakan salahsatu cerita fiksi dari Timur Tengah yang menarik untuk dikaji. Tokoh utama dalam cerpen FSmemiliki kecenderungan kejiwaan yang berbeda dari manusia biasa. Ia diduga mengidap delir danhasrat infantil yang dikuasai oleh mimpinya. Untuk membuktikan fenomena kejiwaan tersebut,penulis melakukan kajian menggunakan pendekatan psikologi Freud. Dalam teorinya Freudmemaparkan konsep id, ego, dan superego, odipus kompleks, dan pemertahan diri. Kajian inimenemukan fenomena kejiwaan tokoh “si pemuda” yang “mencintai” ibunya sehinggamenganggap sang ayah sebagai saingan. Ia juga memiliki hasrat terpendam untuk memilikiseorang wanita berkulit hitam dan dingin seperti patung lilin. Keinginan dan hasrat terpendamtokoh utama dalam FS memperlihatkan fenomena delir dan hasrat infantil yang ada pada diri sipemuda.